Adopsi, Implementasi, dan Integrasi Teknologi dalam Tridarma Perguruan Tinggi untuk Smart Campus - Koesanto, Stefani Made Ayu Artharini; Wiradharma, Gunawan; Prasetyo, Mario Aditya; Fauzi, Luthfi Faishal (Universitas Muhammadiyah Magelang, 2026)
The transformation towards a smart campus is no longer an option, but an urgent necessity for universities in Indonesia to survive and excel in the digital age. The implementation of technology in the three pillars of higher education is key to improving efficiency, educational quality, and global competitiveness. This study aims to examine the adoption, implementation, and integration of technology in the implementation of the three pillars in Indonesian universities using a qualitative approach. The results of the study show the formation of a digital learning ecosystem model consisting of the following main components: strong technological infrastructure (campus internet and Wi-Fi); hardware and software, such as LMS; competent human resources through continuous training; and active student involvement in digital learning. Other components that support this ecosystem include digital content, data-based evaluation, institutional policies such as green technology, system interoperability, and digital communication tools. The main challenges in implementation are uneven digital literacy, funding constraints, and resistance to change. However, through regular training strategies, policy strengthening, and inclusive change management, smart campuses in Indonesia have the potential to become a key strategy for creating adaptive, innovative, and globally competitive higher education.